Analisis Minat Masyarakat dalam Membayar Zakat Secara Online di BAZNAS (Studi Kasus BAZNAS Kabupaten Pinrang) - Sri Rahayu; Wahyuni; Andi Bisyriani (Mappideceng:Jurnal Ekonomi Syariah, 2024)
The development of digital technology encourages innovation in religious services, including zakat payment. BAZNAS Pinrang Regency has provided online zakat payment services to facilitate the community. This study aims to analyze public interest in paying zakat online at BAZNAS Pinrang Regency with a qualitative approach and case study method. Data were obtained through interviews with potential community members as muzakki, BAZNAS administrators, and other related parties, as well as through observation and document analysis. The results showed that community interest still varies. Some people are interested because of the convenience and practicality of the online system, while others continue to choose conventional methods due to habits and limitations in understanding technology. The main obstacles include low digital literacy, limited internet access in some areas, and lack of trust in the online system, so direct payments are considered safer and more convenient for some people.